A Survey on Three-Dimensional Wireless Ad Hoc and Sensor Networks - Babar Shah; Ki-Il Kim (International Journal of Distributed Sensor Networks)
In parallel with steady research and development in ad hoc and wireless sensor networks, many testbeds have been implemented and deployed in real world. Furthermore, some research works have addressed design issues for deployment in three-dimensional space such as sky or ocean. Since many research challenges in three-dimensional spaces have not been explored yet as much as two dimensional spaces, it is required to define the challenging tasks to provide reliable communication in three-dimensional space. In this survey, we aim to identify the unique properties of communication environments in three-dimensional space and address the overview of the state of the art in this research area. To achieve this, the survey is organized according to two good example networks, airborne ad hoc networks (AANETs) and underwater wireless sensor networks (UWSNs). For each network, we introduce and review the related research works to focus on infrastructure, localization, topology design, and position-based routing. Finally, open research issues are also discussed and presented.